2007
DOI: 10.1111/j.1365-294x.2007.03449.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical and biological determinants of genetic diversity in the highly endemic triploid sea lavender Limonium dufourii (Plumbaginaceae)

Abstract: Microsatellite markers were used to evaluate the genetic diversity and population genetic structure in the critically endangered Limonium dufourii (Plumbaginaceae), a highly endemic triploid species from the coasts of eastern Spain. Sixty-five alleles from 13 microsatellite regions were amplified in a sample of 122 individuals collected from the six extant populations. Microsatellite patterns were consistent with the triploid nature of L. dufourii. Alleles were unambiguously assigned to two different parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Poor microsatellite transferability results also support the large phylogenetic distance from these two to other Limonium species (Palop et al 2000). Therefore, if other unrelated Limonium species would have been involved in the origin of L. narbonense, microsatellite amplification patterns should have revealed a high proportion of null alleles, due to the amplification of only one subgenome (Palop-Esteban et al 2007); fixed banding profiles, due to the absence of recombination between heterologous chromosome pairs; or absence of allele variability in one or both subgenomes (Palop-Esteban et al 2007). None of these patterns was observed in the electropherograms of L. narbonense (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Poor microsatellite transferability results also support the large phylogenetic distance from these two to other Limonium species (Palop et al 2000). Therefore, if other unrelated Limonium species would have been involved in the origin of L. narbonense, microsatellite amplification patterns should have revealed a high proportion of null alleles, due to the amplification of only one subgenome (Palop-Esteban et al 2007); fixed banding profiles, due to the absence of recombination between heterologous chromosome pairs; or absence of allele variability in one or both subgenomes (Palop-Esteban et al 2007). None of these patterns was observed in the electropherograms of L. narbonense (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, genetic diversity in Limonium may be conditioned not only by extrinsic factors, such as distribution ranges, but also by intrinsic factors such as ploidy levels and reproductive system types. Accordingly, L. dufourii (Girard) Kuntze, the only species studied to date using microsatellite markers, showed lower genotypic diversity and a stronger population differentiation than L. narbonense (72.06 vs. 18.82% of the variance distributed among populations; see Palop-Esteban et al 2007 and Table 2), as consequence of triploidy, which involves male sterility, absence of recombination at meiosis, and exclusively apomictic reproduction. Fixation indices (F IS ) do not provide support for nonrandom mating and asexual reproduction in L. narbonense.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Conservation and restoration strategies for endangered clonal plants must pay careful attention to genetic diversity of the population (e.g., Palop-Esteban et al 2007;Rasmussen and Kollmann 2008). Our data revealed that the genetic diversity and integrity of populations of the clonal salt-marsh sedge C. scabrifolia differ greatly, irrespective of population size.…”
Section: Resultsmentioning
confidence: 80%